Reforms in the Health System of Uzbekistan - Khuzhanazarov A. Z (Researchparks Publishing, 2022)
This article is devoted to the history medicine in our country, as well as the development and problems that have arisen in medicine and ways to solve them. The health care system is analyzed, reforms have been carried out in recent years and the role of modern medicine in maintaining the health of the people. Questions were also analyzed, such as the fact that problems in the field of medicine are solved through reforms carried out during the years of independence. Comprehensive measures and conceptual programs are also outlined aimed at improving the quality of medical services provided to the population in our country, strengthening the human resources of the healthcare system, and improving the material base of medical institutions.